A condiment that calls - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Ahmed Idris Hassen, from the Department of Biology at Alemaya University in Ethiopia, reminds us that 'in many African countries, most staple foods and condiments are the results of microbial fermentations, and Ethiopia is no exception. In the...